Analisis lingkungan pada rencana strategi bank syariah terkemuka di Indonesia - Rabhita, Fatimah Tasya; Asfarina, Fathya Zulva; Hanifah, Nurul (Maliki Interdisciplinary Journal, 2023)
This journal discusses the important role of banking in a country's economic progress, with a focus on the development of sharia banking in Indonesia. Along with the rapid growth of the financial sector, both in terms of individuals and institutions, this article discusses conventional banks and Islamic banks, with Islamic banks operating based on Islamic sharia principles. Apart from that, this article explains the vision, mission and strategic plans of Bank Mega Syariah, Bank Muamalat and Bank BCA Syariah. This plan includes increasing human resource capabilities, developing banking products and services, sustainability, process optimization and good corporate governance. The research results also include an analysis of the internal and external environment of the three Islamic banks.